2020
DOI: 10.22270/ajprd.v8i3.712
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Ethanol Extract of Rhizome Turmeric (Curcuma Longa L.) For Growth of Escherichia coli, Staphylococcus aureus and Candida albicans

Abstract: Objective: The purpose of this study was to determine at what concentration of ethanol extract of rhizome turmeric is active against Escherichia coli, Staphylococcus aureus and Candida albicans. Methods: Ethanolic extract of rhizome turmeric was tested for phytochemical screening by using standard protocol. Antimicrobial testing was using the diffusion disc method to measure the inhibition zone against the Escherichia coli, Staphylococcus aureus and Candida albicans with various concentration of rhizome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A large number of side effects during application, as well as the high price of synthetic compounds, resulted in the tendency of many researchers to search for efficient natural products. Kasta [17] investigating the necessary concentration and antimicrobial activity of the ethanolic extract of the rhizome of turmeric (Curcuma Longa L.) for the growth of Escherichia coli, Staphylococcus aureus and Candida albicans used Disk diffusion method to measure the zone of inhibition with different concentrations of turmeric rhizome extract (500 mg/mL, 400 mg/mL, 300 mg/mL, 200 mg/mL, 100 mg/mL, 50 mg/mL and 25 mg/mL). The results of phytochemical screening showed that the ethanolic extract of turmeric rhizomes contains alkaloids, flavonoids, saponins, tannins and triterpenoids/steroids, while the antimicrobial inhibition of the ethanolic extract of turmeric rhizomes against Escherichia coli, Staphylococcus aureus and Candida albicans at a concentration of 500 mg/mL was 15,88 mm, 15,63 mm and 15,22 mm.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of side effects during application, as well as the high price of synthetic compounds, resulted in the tendency of many researchers to search for efficient natural products. Kasta [17] investigating the necessary concentration and antimicrobial activity of the ethanolic extract of the rhizome of turmeric (Curcuma Longa L.) for the growth of Escherichia coli, Staphylococcus aureus and Candida albicans used Disk diffusion method to measure the zone of inhibition with different concentrations of turmeric rhizome extract (500 mg/mL, 400 mg/mL, 300 mg/mL, 200 mg/mL, 100 mg/mL, 50 mg/mL and 25 mg/mL). The results of phytochemical screening showed that the ethanolic extract of turmeric rhizomes contains alkaloids, flavonoids, saponins, tannins and triterpenoids/steroids, while the antimicrobial inhibition of the ethanolic extract of turmeric rhizomes against Escherichia coli, Staphylococcus aureus and Candida albicans at a concentration of 500 mg/mL was 15,88 mm, 15,63 mm and 15,22 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Then the antibacterial activity was determined from the clear zone (inhibition zone) which was measured with a caliper. Repeats and measurements were three times repetition (Ghosh et al 2008;Kasta 2020;Harahap et al 2021). The significance level between treatments was determined using a one-way ANOVA analysis with p < 0.05.…”
Section: Determination Of Activity As Antibacterialmentioning
confidence: 99%
“…Based on the results of phytochemical screening that has been carried out the crown of roselle (Hibiscus sabdariffa L.) contains compounds flavonoids, saponins, and tannins. Flavonoids have antibacterial activity because of the ability of flavonoids to interact with cell membranes and affect cell membrane bioactivity and it has been reported that flavonoids are able to reduce the fluidity of bacterial cell membranes that is directly related to damage to cytoplasmic membranes or indirect damage H. Purba et al Phytochemical screening of bunga rosella through autolysis/weakening of the cell wall and consequently osmotic lysis (Gurning, 2020;Simanjuntak, 2020;Wu et al 2013).…”
Section: Minimun Inhibitory Concentrationmentioning
confidence: 99%
“…Antibacterial activity from natural product has been growing rapidly the past few years. Bioactive compound of these natural product as antimicrobial activity has been publicated (Gurning, 2020). Rosella (Hibiscus sabdariffa L.) is a plant of the tropics and sub-tropics, including Indonesia.…”
Section: Introductionmentioning
confidence: 99%